Accuracy of near‐patient vs. inbuilt spirometry for monitoring tidal volumes in an in‐vitro paediatric lung model. (1st March 2018) - Morgenroth, S.; Thomas, J.; Cannizzaro, V.; Weiss, M.; Schmidt, A. R.
Summary: Spirometric monitoring provides precise measurement and delivery of tidal volumes within a narrow range, which is essential for lung‐protective strategies that aim to reduce morbidity and mortality in mechanically‐ventilated patients. Conventional anaesthesia ventilators include inbuilt spirometry to monitor inspiratory and expiratory tidal volumes. The GE Aisys CS 2 anaesthesia ventilator allows additional near‐patient spirometry via a sensor interposed between the proximal end of the tracheal tube and the respiratory tubing. Near‐patient and inbuilt spirometry of two different GE Aisys CS 2 anaesthesia ventilators were compared in an in‐vitro study. Assessments were made of accuracy and variability in inspiratory and expiratory tidal volume measurements during ventilation of six simulated paediatric lung models using the ASL 5000 test lung. A total of 9240 breaths were recorded and analysed. Differences between inspiratory tidal volumes measured with near‐patient and inbuilt spirometry were most significant in the newborn setting (p < 0.001), and became less significant with increasing age and weight. During expiration, tidal volume measurements with near‐patient spirometry were consistently more accurate than with inbuilt spirometry for all lung models (p < 0.001). Overall, the variability in measured tidal volumes decreased with increasing tidal volumes, and was smaller with near‐patient than with inbuilt spirometry. The variability in measured tidal volumes was higher during expiration, especially with inbuilt spirometry. In conclusion, the present in‐vitro study shows that measurements with near‐patient spirometry are more accurate and less variable than with inbuilt spirometry. Differences between measurement methods were most significant in the smallest patients. We therefore recommend near‐patient spirometry, especially for neonatal and paediatric patients.